Local Perceptions of Forest Certification in State-Based Forest Enterprises - Şen, Gökhan; Güngör, Ersin (Springer Science and Business Media LLC, 2018)
Forest management certification plays a supportive role in the realization of wood production by evaluating social, economic and ecological objectives. This study analyzed the changes in the perceptions, views and expectations with respect to forest management certification held by those who live on forest land in Turkey, known as forest peasants, according to their education level, age and their engagement in forestry activities. The study was conducted at the Kastamonu Regional Directorate of Forestry located in northwestern Turkey. Data were collected using face-to-face survey with 407 forest peasants who randomly selected. In addition to the descriptive statistics, Kruskal–Wallis and Mann–Whitney U tests were used to analyze whether there were any significant differences among the views depending on the locals’ education level, age and their engagement in forestry activities. The results showed that forest peasants generally knew what certification was. The forest peasants stated that certification has benefits for occupational health and safety. However, they also stated that there had not been any significant increase in forestry worker wages or the price of forest products, that there had not been any noticeable difference in the forest administration’s forestry activities, and that the principles of participatory forest management had not been applied efficiently and effectively following certification.
Keywords: Forest Stewardship Council (Fsc); Local People's Perceptive; Sustainable Forestry; Turkey; State Forestry; Forestry; 4. Education; 15. Life on land